The efficacy of combining paraffin oil with conventional fungicide treatments against grape powdery mildew in Eger - Pálfi, Xénia; Karácsony, Zoltán; Kátai, János; Zsófi, Zsolt (Acta Agraria Debreceniensis, 2022)
We aimed to test the combination of paraffin oil (PFO) with regular fungicide treatment to assess its efficacy against grape powdery mildew (GPM) in a small spraying experiment on two Vitis vinifera L. cultivars (Chardonnay and Kékfrankos) with different susceptibility to Erysiphe necator. The visual symptoms of GPM on leaves and clusters were examined at three phenological states. The harvest yield was characterized by two methods, data were analyzed with one-way ANOVA and Tukey post-hoc test. Regular fungicide treatment (CT) and its combinations with PFO showed better results in both varieties to repress GPM in 2015 relative to sole PFO treatments. Mean values of combined treatments were often lower than CT but did not differ significantly from each other. The same was observed in 2016, despite the higher pressure of GPM, and missed the third survey. No significant differences were detected between treatments in yield. In contrast, the mean cluster weight of CT and combined treatments resulted in (insignificantly) higher values in each variety and year. In summary, the sole PFO showed some disease control capability as reported earlier, but this effect was greatly affected by the given vintage. Combining PFO with CT resulted in increased protection against GPM relative to the solely applied fungicides. However, this effect was not significant in all cases. It also depended on the vintage and cultivar characteristics. The beneficial impact of paraffin oil as an additive to CT may be due to the induction of plant stress responses and/or its ability to support the adherence and absorption of the combined agents.